Defective Ristocetin-Induced Platelet Aggregation in von Willebrand's Disease and its Correction by Factor VIII - Weiss, Harvey J. (1973)
The antibiotic ristocetin, in concentrations of 1.0-1.5 mg/ml, aggregated normal platelets in citrated platelet-rich plasma by a mechanism in which the release reaction played only a minor role. Platelet aggregation by ristocetin in a concentration of 1.2 mg/ml was absent or markedly decreased in 10 patients with von Willebrand's disease. Lesser degrees of abnormality were obtained with a concentration of 1.5 mg/ml. The magnitude of the defect in ristocetin-induced platelet aggregation correlated well with the degree of abnormality of the bleeding time and the levels of antihemophilic factor (AHF, VIII(AHF)) procoagulant activity. In all patients, the defect in ristocetin-induced platelet aggregation was corrected in vitro by normal plasma. Correction was also obtained with a fraction of normal cryoprecipitate that eluted in the void volume with VIII(AHF) after chromatography on a gel that excludes molecules larger than 5 × 10(6). A similar fraction, devoid of VIII(AHF) activity, obtained from patients with von Willebrand's disease had no corrective effect, but fractions obtained from patients with hemophilia were just as effective as those obtained from normal subjects. The correction activity of plasma and partially purified factor VIII was inhibited by a rabbit antibody to human factor VIII but not by a human antibody against VIII(AHF) procoagulant activity. The studies provide further evidence that patients with von Willebrand's disease are deficient in a plasma factor that is necessary for normal platelet function. The activity of this factor appears to be associated with factor VIII but is unrelated to VIII(AHF) procoagulant activity.